Video Learning Media Improves Science Process Skills in Primary Students: Media Pembelajaran Video Meningkatkan Keterampilan Proses Sains pada Siswa Sekolah Dasar - Jahro, Aminatin Chusniatu; Setiyawan, Enik (Indonesian Journal of Education Methods Development, 2026)
This study examines the integration of multimedia learning in elementary science instruction. General Background: Science education at the primary level emphasizes the development of science process skills as a foundation for conceptual understanding and scientific reasoning. Specific Background: However, classroom observations indicate that students tend to be passive and rely heavily on textbooks, resulting in limited engagement and low science process skill performance. Knowledge Gap: Previous studies have explored video-based instruction, yet limited research has comprehensively assessed seven indicators of science process skills using researcher-designed instructional videos in ecosystem topics. Aims: This study aims to determine whether video learning media contributes to differences in science process skills among fifth-grade students. Results: Using a quasi-experimental Non-Equivalent Control Group Design with 52 students, statistical analysis through Paired Sample T-Test and Independent Sample T-Test revealed a significant difference (Sig. 0.000 < 0.05), with the experimental group achieving higher post-test scores (85.54) than the control group (78.00). Novelty: The study integrates seven complete science process indicators and employs self-developed animated videos enriched with educational songs on ecosystem material. Implications: Findings provide empirical evidence supporting multimedia-based science instruction as a practical strategy to foster active engagement and strengthen science process competencies in primary education. Keywords: Video Learning Media, Science Process Skills, Primary Science Education, Quasi Experimental Design, Ecosystem Learning Key Findings Highlights Experimental group demonstrated statistically higher post-test performance than control group Seven complete process indicators were systematically measured through structured assessment Animated ecosystem materials increased classroom engagement and active participation